IMPACT OF RAIDING ON THE FINANCIAL SECURITY OF BUSINESS ENTITIES (World of finance, 2023)
Introduction. The scale of raiding and the pace of its spread in the economic system of a particular country are determined by such main factors as: the quality of the legislative framework, which regulates various aspects of the financial activity of economic entities; a mechanism for protecting property rights; the effectiveness of state institutions for the protection of property rights; separation of business from politics; the state of corruption manifestations in the activities of state authorities, especially the judiciary; transparency of privatization processes; the level of development of corporate control in the middle of enterprises; transparency of financial flows of business entities; level of legal culture of business structures.The purpose of the article is to determine the theoretical and applied aspects of the emergence of raiding threats to business structures and to develop an effective mechanism for countering raiding as a component of the strategy for ensuring the financial security of economic entities.Results. The concept of raiding and modern problems of protecting business entities from this phenomenon are studied. The domestic realities of manifestations of raiding and the main objects of raiding attacks in Ukraine are analyzed. Measures to protect against raiding have been disclosed, which should be individual for each economic entity, taking into account the specifics of its activity.Conclusions. Proposals for effective implementation of methods of confrontation, protection of business owners from raider attacks and strengthening of financial security of business entities are substantiated. Since raiding is an acute problem both for business (which takes away corporate rights and assets) and for the state (which loses the opportunity to invest in the development of the economy), it is advisable to oppose this phenomenon by increasing the level of financial security by using the efforts of both business structures, as well as state institutions.